Agriculture land management in Gorontalo Province - Putri, R.F. (IOP Publishing Ltd, 2021)
Gorontalo is the smallest province in Sulawesi Island with the higher population density than three other provinces. But, it has large agriculture area with the corn as the highest exported commodity in 2019. Most of people in Gorontalo Province are working in agriculture sector. Although the number of population are increasing every year, the agriculture land are still existing in Gorontalo Province. This study focuses on population dynamic and agriculture land management in Gorontalo. Secondary data from Statistic Board Center of Indonesia are used to assess the population dynamic, such as population growth rate, population density, and population pressure on the agriculture land. We used time series data from 2008 until 2017. The data then analyzed with descriptive quantitative method by discussing the results of data calculation. The results show that although there is an increasing of population density in Gorontalo Province, but the population pressure is low. The optimum development on agriculture sector in Gorontalo Province affect the high productivity on many agricultural commodities, especially for corn crop. So, the agriculture land area are still prioritized in this region. Â© Published under licence by IOP Publishing Ltd.